Shoots and Turions of Aquatic Plants as a Source of Fatty Acids - Strzemski, Maciej; Adamec, Lubomir; Dresler, Sławomir; Mazurek, Barbara; Dubaj, Katarzyna; Stolarczyk, Piotr; Feldo, Marcin; Płachno, Bartosz J (Molecules (Basel, Switzerland), 2024)
BACKGROUND: Fatty acids are essential for human health. Currently, there is a search for alternative sources of fatty acids that could supplement such sources as staple crops or fishes. Turions of aquatic plants accumulate a variety of substances such as starch, free sugars, amino acids, reserve proteins and lipids. Our aim is to see if turions can be a valuable source of fatty acids. METHODS: Overwintering shoots and turions of aquatic carnivorous plants were collected. The plant material was extracted with hexane. The oils were analyzed using a gas chromatograph with mass spectrometer. RESULTS: The dominant compound in all samples was linolenic acid. The oil content was different in turions and shoots. The oil content of the shoots was higher than that of the turions, but the proportion of fatty acids in the oils from the shoots was low in contrast to the oils from the turions. The turions of Utricularia species were shown to be composed of about 50% fatty acids. CONCLUSIONS: The turions of Utricularia species can be used to obtain oil with unsaturated fatty acids. In addition, the high fatty acid content of turions may explain their ability to survive at low temperatures.
Keywords: Aldrovanda; plynová chromatografie s hmotnostně spektrometrickou detekcí; Myriophyllum; aquatic plants; alpha-Linolenic Acid; Plant Oils; Stratiotes; Utricularia; oleje rostlin; Fatty Acids; Plant Shoots; turions; Gas Chromatography-Mass Spectrometry; kyselina alfa-linolenová; GC-MS analysis; essential fatty acid; mastné kyseliny; výhonky rostlin